Inhibition of viral suppressor of RNAi proteins by designer peptides protects from enteroviral infection in vivo - Fang,Y; Liu,Z; Qiu,Y; Kong,J; Fu,Y; Liu,Y; Wang,C; Quan,J; Wang,Q; Xu,W; Yin,L; Cui,J; et al. (Immunity, 2021)
RNA interference (RNAi) is the major antiviral mechanism in plants and invertebrates, but the absence of detectable viral (v)siRNAs in mammalian cells upon viral infection has questioned the functional relevance of this pathway in mammalian immunity. We designed a series of peptides specifically targeting enterovirus A71 (EV-A71)-encoded protein 3A, a viral suppressor of RNAi (VSR). These peptides abrogated the VSR function of EV-A71 in infected cells, and resulted in the accumulation of vsiRNAs and reduced viral replication. These vsiRNAs were functional, as evidenced by RISC-loading and silencing of target RNAs. The effects of VSR-targeting peptides (VTPs) 32 on infection with EV-A71 as well as another enterovirus, Coxsackievirus-A16, were ablated upon deletion of Dicer1 or AGO2, core components of the RNAi pathway. In vivo,VTP treatment protected mice against lethal EV-A71 challenge, with detectable vsiRNAs. Our findings provide evidence for the functional relevance of RNAi in mammalian immunity and present a therapeutic strategy for infectious disease.